Vertical integration in a stochastic framework and a nonsymmetric bargaining equilibrium - Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
We go through the decision to vertically integrate or outsource in an uncertain framework. We consider two different market strategies, price setting and quantity setting and two different vertical relationships: a Stackelberg one and a bargaining one. In the first scenario, with certainty, price and quantity settings are alike, while with uncertainty the ranking changes. If the bargaining framework is adopted instead, quantity setting under uncertainty leads to an asymmetric distribution of realized gains along the vertical chain.
Keywords: 330; Vertikale Integration; Outsourcing; Nash-Gleichgewicht; Duopol; Theorie